Conception of tuberculosis and evidence from slum area - Sultana, Nasrin; Tania, Fatema (International Journal Of Community Medicine And Public Health, 2017)
Background: Tuberculosis (TB) remains as an important public health problem in Bangladesh. TB is an infectious bacterial disease caused by Mycobacterium tuberculosis, which most commonly affects the lungs. The common symptoms of tuberculosis include cough for a prolonged duration that is more than three weeks, unexplained or intended weight loss, fatigue, general feeling of tiredness, fever, sweating at night, chills and loss of appetite. The patients of Tuberculosis hide their disease from family, relatives, and community due to the presence of misconception. Methods:This cross-sectional study was done with 103 respondents .The objectives of this study were to assess knowledge of TB patients about their disease, and to identify their misconceptions associated with TB. The study was conducted to identify the conception regarding tuberculosis among the slum dweller in Shyamoli and Mohammmadpur area, in Dhaka city. Data were collected by face to face interview using semi-structured questionnaire. Results: Out of 103 respondents, among them 48.5% were in 15-25 years age group with mean 26.15; (SD = ± 5.34). More than two fifth (53.4%) respondents were male and 46.6t were female and 53.41% were educated up to primary level, 71.84% were married, 88% were Muslims, 26.21% respondents were Garment worker, 60.0% were lived in a nuclear family. Majority respondents (86.41%) live in tin shade house. Among the respondents 53.4% heard about TB disease and the main source of information was mass media(TV, Radio).Majority(70.87%) of respondents knew that Cough for more than 2 weeks is the Common Symptom of TB. Conclusions:Study findings shows that there is lots of misconception about tuberculosis but various TB control program are running in Bangladesh by Gob and different NGOs which can be help the people of our country to overcome the problems.